Development and evaluation of pneumatic packaging machine for paddy - FASEERA A.C MIKHAIL P.J SWATHA V.S; Dr. P.K Sureshkumar (Guide) (Tavanur 2013 Kelappaji College of Agricultural Engineering and Technology)
Development and evaluation of pneumatic packaging machine for paddy
Development and evaluation of pneumatic packaging machine for paddy